2003
DOI: 10.1097/00007435-200304000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Sexually Transmitted Diseases (STDs) in Female Sex Workers

Abstract: Strengthened periodic screening for and treatment of confirmed STD, in addition to condom promotion and provision, represent feasible, effective interventions in commercial sex, and time series analyses can provide a useful approach to evaluating new interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Our estimate of 9% syphilis seroprevalence is comparable with an 11% estimate from the mid-1990s [4], but higher than the 3.3% reported earlier that decade [2] and 4.1% identified among primarily registered sex workers [30]. Our study reports no evidence of recent syphilis, consistent with an interpretation of low frequency of transmission.…”
Section: Discussionsupporting
confidence: 87%
“…Our estimate of 9% syphilis seroprevalence is comparable with an 11% estimate from the mid-1990s [4], but higher than the 3.3% reported earlier that decade [2] and 4.1% identified among primarily registered sex workers [30]. Our study reports no evidence of recent syphilis, consistent with an interpretation of low frequency of transmission.…”
Section: Discussionsupporting
confidence: 87%
“…The intervention group underwent a 6-month program of educational videos, small group discussions, educational materials, received free condoms, and it found incidences of 0.04 compared to 0.12 per person-year of follow-up among intervention and control women, respectively [15]. The second reported that long-term consistent condom use had protective effect for anti-HBc positivity among FSW participating in a control program in Peru [34]. However, two additional studies carried out in other populations found conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is response to antibiotics in many women, persistence or recurrence of the condition occurs in 11%–29% of women at 1 month [104, 108, 109]. Moreover, long-term recurrence rates have been shown to be greater than 70% [19, 110, 111]. Marrazzo et al [63] investigated several risk factors for BV persistence one month after treatment, including the detection of key vaginal bacteria by species-specific PCR.…”
Section: Molecular Studies In the Vaginal Niche: A Critical Examinmentioning
confidence: 99%